2022
DOI: 10.1126/scitranslmed.abn8057
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing antibody responses elicited by SARS-CoV-2 mRNA vaccination wane over time and are boosted by breakthrough infection

Abstract: The waning efficacy of SARS-CoV-2 vaccines, combined with the continued emergence of variants resistant to vaccine-induced immunity, has reignited debate over the need for booster vaccine doses. To address this, we examined the neutralizing antibody response against the spike protein of five major SARS-CoV-2 variants, D614G, Alpha (B.1.1.7), Beta (B.1.351), Delta (B.1.617.2), and Omicron (B.1.1.529), in health care workers (HCWs) vaccinated with SARS-CoV-2 mRNA vaccines. Serum samples were collected pre-vaccin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
163
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 183 publications
(187 citation statements)
references
References 36 publications
22
163
1
1
Order By: Relevance
“…These results agree with the findings of a recent study that reported a marked boosting effect on the titer of anti-S protein RBD antibody 1 week after the second dose in people with and without DM [13]. Furthermore, in agreement with recent reports that examined humoral immune response prospectively up to 6 months post-vaccination [14,15], we found a significant decline in Abs-RBD-IgG two months after the second dose of the vaccine.…”
Section: Discussionsupporting
confidence: 93%
“…These results agree with the findings of a recent study that reported a marked boosting effect on the titer of anti-S protein RBD antibody 1 week after the second dose in people with and without DM [13]. Furthermore, in agreement with recent reports that examined humoral immune response prospectively up to 6 months post-vaccination [14,15], we found a significant decline in Abs-RBD-IgG two months after the second dose of the vaccine.…”
Section: Discussionsupporting
confidence: 93%
“…36 33 [27- 25 [23][24][25][26][27][28] 26 [22][23][24][25][26][27] 22 [24][25][26] 26 [24][25][26][27][28] 27 [24][25][26][27][28][29][30][31][32][33][34][35] 22 [21][22][23][24] 32 [26][27][28][29][30][31][32][33][34] 26 [25][26][27][28][29][30][31]…”
Section: Age Median Years [Iqr]unclassified
“…Currently available vaccines are based on the ancestral Wuhan-Hu-1 strain and induce antibodies with a neutralizing capacity that exceeds the breadth elicited by infection with the Wuhan strain, or with variants of concern (VOCs) (3). However, protective titers wane over time (4)(5)(6)(7) and routine booster vaccinations are thought to be needed to trigger recall immunity and maintain efficacy against new VOCs (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%